2008
DOI: 10.1007/s00066-008-1770-1
|View full text |Cite
|
Sign up to set email alerts
|

Multisegmented Tangential Breast Fields: a Rational Way to Treat Breast Cancer

Abstract: MS-CRT is a good alternative to breast intensity-modulated radiation therapy (IMRT) and seems adequate for right-sided cancers, whereas left-sided cancers necessitate a longer follow-up of heart-related side effects before a final assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The optimization of dose was performed with forward planned segments delivered in step-and-shoot technique [27,36]. The results of the presented study are consistent with several published reports showing that the majority of applications of intensity-modulated radiotherapy to tangential breast radiotherapy resulted in improvements to the dose distribution over the standard wedge pair [1,6,9,14,18,29,35]. Recently, a randomized study suggested that this dosimetric difference transfers into a clinical benefit by reducing acute skin toxicity compared to the traditional wedge technique [22].…”
Section: Discussionsupporting
confidence: 77%
“…The optimization of dose was performed with forward planned segments delivered in step-and-shoot technique [27,36]. The results of the presented study are consistent with several published reports showing that the majority of applications of intensity-modulated radiotherapy to tangential breast radiotherapy resulted in improvements to the dose distribution over the standard wedge pair [1,6,9,14,18,29,35]. Recently, a randomized study suggested that this dosimetric difference transfers into a clinical benefit by reducing acute skin toxicity compared to the traditional wedge technique [22].…”
Section: Discussionsupporting
confidence: 77%
“…For disease of the left breast, the doses are usually higher but vary widely, and for some women, including those in whom the distance of the heart to the thoracic wall is small and those who require internal mammary irradiation, the mean dose may be around 10 Gy. [5][6][7][8][9][10][11] Among the 2168 women in this study, the mean dose to the heart ranged from 0.03 Gy to 27.72 Gy, with an overall average of the mean doses of 4.9 Gy. The risk of a major coronary event increased linearly with the mean dose to the heart.…”
Section: Discussionmentioning
confidence: 99%
“…4 Nevertheless, in most women, the heart still receives doses of 1 to 5 Gy. [5][6][7][8][9][10][11] Several studies have suggested that exposures at this level can cause is che mic heart disease, [12][13][14] but the magnitude of the risk after any given dose to the heart is uncertain, as are the time to the development of any radiation-related disease and the influence of other cardiac risk factors. We therefore conducted a study relating the risk of is chemic heart disease after radiotherapy to each woman's radiation dose to the heart and to any cardiac risk factors she had at the time of radiotherapy.…”
mentioning
confidence: 99%
“…Concerning large breast volumes, some efforts should be made to reduce the dose to the organs at risk [2][3][4] and to avoid hot spots within the target to prevent cardiac failure, secondary lung cancer, acute toxicity and impaired cosmetics [5][6][7]. To achieve these requirements various solutions exist, including the use of advanced radiotherapy techniques with or without deep inspiration breath-hold [8][9][10] or changing treatment position [5,11] or both [9,12,13]. One promising all-in-one solution could be the prone position.…”
Section: Introductionmentioning
confidence: 99%